1988
DOI: 10.1007/bf00173408
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensinogen gene expression in extrahepatic rat tissues: Application of a solution hybridization assay

Abstract: Angiotensin II has numerous biological effects in a hitherto unsuspected variety of tissues. The generation of angiotensin in tissue requires the local presence of its high molecular weight precursor angiotensinogen and is best tested by investigating angiotensinogen gene expression. A quantitative solution hybridization assay for rapid and sensitive measurement of angiotensinogen mRNA was therefore established to study the extrahepatic expression of the angiotensinogen gene. We used a 714 bases BamHI angioten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
44
0

Year Published

1989
1989
2000
2000

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 90 publications
(46 citation statements)
references
References 23 publications
2
44
0
Order By: Relevance
“…The detection of renin mRNA by in situ hybridization experiments in cells identified as gonadotropes (Deschepper et al 1986b) provides further evidence against an internalization of circulating RAS components in pituitary cells. Furthermore, AGT mRNA has also been detected in pituitary cell extracts, both by a solution hybridization assay (Hellmann et al 1988) and by RT-PCR (Sernia 1995).…”
Section: Discussionmentioning
confidence: 99%
“…The detection of renin mRNA by in situ hybridization experiments in cells identified as gonadotropes (Deschepper et al 1986b) provides further evidence against an internalization of circulating RAS components in pituitary cells. Furthermore, AGT mRNA has also been detected in pituitary cell extracts, both by a solution hybridization assay (Hellmann et al 1988) and by RT-PCR (Sernia 1995).…”
Section: Discussionmentioning
confidence: 99%
“…Hellmann et al 13 showed that angiotensinogen is expressed within the vessel wall. Naftilan and colleagues extended these observations by means of in situ hybridization.…”
Section: Discussionmentioning
confidence: 99%
“…in the brush border membranes of the intestine (Ward et al, 1980). It has been demonstrated that angiotensinogen can be synthesized in extrahepatic tissues such as the aorta (Hellmann et al, 1988). In addition, renin was found to be synthesized in aortic smooth muscles (Re et al, 1982).…”
Section: Discussionmentioning
confidence: 99%